2018
DOI: 10.21873/anticanres.12432
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of Novel Bone-seeking, α-emitting 224Ra-solution in a Breast Cancer Skeletal Metastases Model

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…Samarium lexidronam ( 153 Sm-EDTMP) is approved worldwide for the pain relief of osteoblastic metastatic bone lesions. While radium itself is inherently a bone-seeker, EDTMP has been used to increase the proportion of daughter nuclides 212 Pb and 212 Bi delivered to the bone in mouse models [ 19 , 20 ]. However, if the goal is to ensure radionuclide accumulation at other target sites, the complexation and bone-seeking properties may be problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Samarium lexidronam ( 153 Sm-EDTMP) is approved worldwide for the pain relief of osteoblastic metastatic bone lesions. While radium itself is inherently a bone-seeker, EDTMP has been used to increase the proportion of daughter nuclides 212 Pb and 212 Bi delivered to the bone in mouse models [ 19 , 20 ]. However, if the goal is to ensure radionuclide accumulation at other target sites, the complexation and bone-seeking properties may be problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Westrom et al investigated the use of Ra-224-coated microparticles for localized internal α-therapy in mice [ 4 , 5 ]. Furthermore, Juzeniene et al showed in a mouse model that Ra-224 is a promising candidate for the treatment of bone metastases related to breast cancer [ 6 ]. These publications highlight the renewed interest in using Ra-224 for clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrated high labelling efficiencies of 224 Ra on the surface of calcium carbonate microparticles with high retention of both 224 Ra and its 212 Pb daughter, and the radioactivity remained primarily localized in the peritoneal cavity [89]. 224 Ra has also been investigated for osteolytic bone metastasis of MDA-MB-231(SA)-GFP-bearing nude mice, decreasing the number and area of tumor foci and prolonging survival [99]. Preclinical diffusing alpha emitters therapy (DaRT) using 224 Ra-loaded wires was tested on mice bearing prostate (PC-3), glioblastoma (GBM, U87-MG), colon (HCT15), squamous cell carcinoma (FaDu), and melanoma (C32) cancer cell tumors.…”
Section: Ramentioning
confidence: 99%